A study of urinary uric acid to creatinine ratio as a biochemical marker of perinatal asphyxia - Chanpura, Vaishali R.; Kacha, Mayur G. (International Journal of Contemporary Pediatrics, 2022)
Background: Perinatal asphyxia remains an important cause of neonatal mortality, morbidity and sequelae especially in developing countries. Prevalence of perinatal asphyxia is 1 to 6 per 1000 live births while incidence of hypoxic-ischemic injury is 0.3 to 2 per 1000 term infants. There was a need to identify neonates with asphyxia at risk for hypoxic ischemic encephalopathy and multi-organ dysfunction using simple bedside tests. The objectives of the study were to evaluate the efficacy of uric acid to creatinine (UA/Cr) ratio in early spot urine samples as a diagnostic tool for perinatal asphyxia and to assess the relationship between urinary UA/Cr ratio and severity of HIE. Methods: This study was conducted on 49 neonates having asphyxia (cases) and 49 neonates without asphyxia (controls) born at a tertiary care hospital over 12 months. Spot urine samples were collected within 24 hours of life and sent for analysis. A UA/Cr ratio of >2.51 was taken as cut-off value. Results: The urinary UA/Cr ratio was found to be higher in asphyxiated infants (2.88±1.01) as compared to the control group (1.72±0.7, p<0.001). UUA/Cr ratio was significantly higher in infants with HIE stage 3 (3.65±1.4) as compared to infants with HIE stage 2 (2.62±0.76) and HIE stage 1 (2.71±0.4) (p<0.009). The cut-off UUA/Cr value of >2.51 has 71.43% sensitivity and 93.88% specificity. Conclusions: The UUA/Cr ratio is a simple and reliable screening test for early diagnosis and assessment of perinatal asphyxia.